2018
DOI: 10.1111/rda.13193
|View full text |Cite
|
Sign up to set email alerts
|

Bovine foetal sex determination—Different DNA extraction and amplification approaches for efficient livestock production

Abstract: Foetal sex determination using polymerase chain reaction (PCR) in mammals is based on the amplification of gender-specific foetal DNA sequences circulating in maternal blood. The bovine synepitheliochorial placenta does not allow a direct contact between the trophoblast and the maternal blood, resulting in difficult passage of foetal DNA and, consequently, its very small amounts in maternal bloodstream. Circulating cell-free foetal DNA (ccffDNA) encompasses short nucleotide fragments (300-600 bp) in maternal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…For the past few decades, many researchers have been dealing with the problem of rendering agricultural and livestock production more effective. Therefore, different methods are used to make animal breeding and animal selection programs more effective [35]. In this study, we investigated the genotype and allelic frequencies of beta-casein gene in 106 Serbian HF cows.…”
Section: Discussionmentioning
confidence: 99%
“…For the past few decades, many researchers have been dealing with the problem of rendering agricultural and livestock production more effective. Therefore, different methods are used to make animal breeding and animal selection programs more effective [35]. In this study, we investigated the genotype and allelic frequencies of beta-casein gene in 106 Serbian HF cows.…”
Section: Discussionmentioning
confidence: 99%
“…During past few decades, molecular markers proved to be an important instrument for selection and preservation of animal populations [1][2][3][4]. Association between DNA polymorphism and milk production traits have been studied for a number of genes, and among them, leptin (LEP) gene proved to be a powerful biomolecule that can increase the productivity of farm animals [5].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed in the present study that the behavior of this protocol as control treatment showed better results when compared to the extraction of DNA from blood cells from the buffalo and cervid species. Variations in the concentration of DNA extracted from the same protocol, in different species, may be related to the divergent leukocyte profile between them (Araújo et al, 2009;Ristanic et al, 2018), since the protocol acts on nucleated cells isolated from the whole blood, which may suffer variations due to external factors, such as stress, causing profile differences among individuals of the same species, albeit in an abnormal way. Caldart et al (2011) evaluated two commercial kits (DNAzol ® -Invitrogen TM , FTA ® -Whatman TM ) for DNA extraction for goat and sheep leukocyte rings as a function of storage time.…”
Section: Resultsmentioning
confidence: 99%
“…The advent of DNA discovery and its applications in molecular sciences made possible some advances in health, research and animal production (Ristanic et al, 2018;Shalaby et al, 2019;Yadav, Tomar, Jha, & Singh, 2017;Yamamoto et al, 2017). However, genetic resources access and use in most of developing countries is lower than expected (Food & Agriculture Organization of the United Nations (FAO, 2010).…”
Section: Introductionmentioning
confidence: 99%